EVALUASI KEBERHASILAN BAURAN PENYEWA MALL KUNINGAN CITY - Sandio Adhya Bayudi; Priyendiswara Agustina Bela; Parino Rahardjo (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
This study aims to determine the right tenant mix for the Kuningan City Mall shopping center in an effort to increase the number of visitors and tenants. Kuningan City Mall has a Lifestyle & Entertainment concept that aims to complement the needs and entertainment for the surrounding area of the Setiabudi District, South Jakarta. In this case, several analyzes are conducted, namely location analysis, market analysis, comparative analysis of Mall Kuningan City with its competitors, and analysis of people's perspectives and perspectives, with the help of several analytical tools to be used namely descriptive, SWOT, comparison method, questionnaire. The analysis results obtained will be used as consideration for a new management strategy for Kuningan City Mall in an effort to increase the number of visitors and tenants. Keywords: competitors; management strategy; occupancy rate; shopping center; tenant mixAbstrakPenulisan ini bertujuan untuk mengetahui bauran penyewa yang tepat bagi pusat perbelanjaan Mall Kuningan City dalam upaya untuk meningkatkan jumlah arus pengunjung dan penyewa. Mall Kuningan City memiliki konsep Lifestyle & Entertainment yang bertujuan untuk melengkapi akan kebutuhan dan hiburan bagi disekitar cakupan area Kecamatan Setiabudi, Jakarta Selatan. Dalam hal ini, maka dilakukan beberapa analisis yaitu analisis lokasi, analisis komparasi antara Mall Kuningan City dengan kompetitornya, dan analisis persepsi dan perspektif masyarakat, dengan bantuan beberapa alat analisa yang akan digunakan yaitu deskriptif, SWOT, comparison method, dan kuesioner. Dari hasil analisis yang diperoleh tersebut akan digunakan sebagai bahan pertimbangan untuk strategi pengelolaan yang baru bagi Mall Kuningan City dalam upaya meningkatkan jumlah arus pengunjung dan penyewa.